Auto-agglutination in albumin - Powell, D. E. B. (1965)
An example of the `albumin' auto-agglutinating phenomenon is reported. This was found in the serum of a man dying from carcinoma of the stomach with liver secondaries. It is suggested that the serum factor is of a protein (probably globulin) nature, and may have been produced by the diseased liver.